Pembuatan Coating Copper-Cobalt Oksida Melalui Proses Sol Gel Dan Dideposisikan Secara Spray Coating Pada Substrat Alumunium - Ramadhan Ramadhan; Amun Amri; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The research aims to synthesis the mixed copper and cobalt oxides coating in alumunium substrate for solar selective absorber (SSA) using sol-gel spray coating method. The coating were characterized using UV-Vis-NIR, X-Ray diffraction, Scan Electron Microscope (SEM) and adhesion test. The sol precursor were copper nitrate and cobalt nitrate. The sol precursor are made by dissolve the granules Cu(NO3)2.3H2O and Co(NO3)2.3H2O into the etanol solvent and added propionate acid. Mix the two solution and then stirred at room temperature for two hours in a closed state. The coating process was done by using a spray gun which is connected by using a compressor. The result of researching showed that sample with precursor concentration 0.25 M and 30 x spraying and drying cycle with (α) = 86.8%. further characteristic was obtained the value of emittance (ε) = 6.64%. The crystal structure of CuCo2O4, CuO and CoCo2O4 were found in XRD result analyst. The result testing of SEM showed that surface coating film relative homogen and the result testing of adhesion showed bond layer of coating categorized as 4B according to the standards ASTM D 3359.Keyword : coating, precursor, sol, solar selective absorber, spray coating